The Phenomenon of Arranged Marriage in the Dieng Community and Its Impact on Marital Harmony: An Islamic Family Counseling Perspective - masduki, Masduki Sidiq Tirmidzi; Ema, Ema Hidayanti; Mita , Mita Putri Apriliani; widayat, Widayat Mintarsih (Universitas Islam Negeri Raden Intan Lampung, 2026)
The phenomenon of arranged marriages in the Dieng Plateau is still a common practice that has been passed down from generation to generation. This study aims to analyze the practice of arranged marriages and their impact on family harmony from the perspective of Islamic Family Guidance and Counseling. The research method used is a qualitative approach with a case study method, involving arranged marriage couples, community leaders, families, and KUA officials as primary informants. The research findings indicate that the practice of arranged marriage has shifted from an authoritative pattern to a more participatory form. However, challenges such as ineffective communication, emotional unpreparedness, and pressure from extended families remain major issues. A systemic and culturally responsive approach to Islamic Family Counseling is needed as a pre-marriage and post-marriage intervention to strengthen family harmony. These findings are expected to serve as a reference for the development of adaptive family counseling services rooted in Islamic values.